Trajectories of Self-Esteem Development for Adolescence Based on China Family Panel Studies: A Piecewise Growth Mixture Model Analysis. (April 2022) - Huang, Jiaqin; Xie, Xin; Pan, Yuxi; Li, Guangming; Zhang, Fadi; Cui, Ningjing
Self-esteem has always been a hot research object in the field of adolescent mental health. But in longitudinal research, using a single slope to describe the trajectory of adolescent self-esteem is unrealistic. The piecewise growth mixture model (PGMM) was used to fit the data in this study. Selecting from China Family Panel Studies database, a total of 1, 759 individuals were selected and their self-esteem (RSES) scores over the years were used as the tracking index. Based on the characteristics of the development trajectories of three latent classes, class 1 was referred to as "stable low level group, " class 2 was named "rapidly rising group, " and class 3 was referred to as "rapidly decrease group." And there were two stages in the development process of self-esteem in the adolescent group. The slope of the stable low level group showed a significant downward trend in the first stage and a significant upward trend in the second stage, with a relatively flat development trajectory and relatively low self-esteem on the whole. The slope of the rapidly rising group showed an insignificant upward trend in the first stage and a significant rapid upward trend in the second stage. The rapidly decrease group showed a significant and rapid downward trend in the first stage and a significant and rapid upward trend in the second stage. In the development of self-esteem in adolescence, there were three latent classes in which the characteristics of development trajectories were different. Age of 14 is the turning point between the two stages of development.